Genome duplication improves rice root resistance to salt stress - Tu, Yi (Springer, 2014)
BACKGROUND: Salinity is a stressful environmental factor that limits the productivity of crop plants, and roots form the major interface between plants and various abiotic stresses. Rice is a salt-sensitive crop and its polyploid shows advantages in terms of stress resistance. The objective of this study was to investigate the effects of genome duplication on rice root resistance to salt stress. RESULTS: Both diploid rice (HN2026-2x and Nipponbare-2x) and their corresponding tetraploid rice (HN2026-4x and Nipponbare-4x) were cultured in half-strength Murashige and Skoog medium with 150 mM NaCl for 3 and 5 days. Accumulations of proline, soluble sugar, malondialdehyde (MDA), Na(+) content, H(+) (proton) flux at root tips, and the microstructure and ultrastructure in rice roots were examined. We found that tetraploid rice showed less root growth inhibition, accumulated higher proline content and lower MDA content, and exhibited a higher frequency of normal epidermal cells than diploid rice. In addition, a protective gap appeared between the cortex and pericycle cells in tetraploid rice. Next, ultrastructural analysis showed that genome duplication improved membrane, organelle, and nuclei stability. Furthermore, Na(+) in tetraploid rice roots significantly decreased while root tip H(+) efflux in tetraploid rice significantly increased. CONCLUSIONS: Our results suggest that genome duplication improves root resistance to salt stress, and that enhanced proton transport to the root surface may play a role in reducing Na(+) entrance into the roots.